Oleuropein as an inhibitor of peroxisome proliferator-activated receptor gamma - Svobodova, Michaela; Andreadou, Ioanna; Skaltsounis, Alexios-Leandros; Kopecky, Jan; Flachs, Pavel (Genes & nutrition, 2014)
Oleuropein, the major phenolic compound found in olive leaves and oil, exerts antioxidant, anti-inflammatory and anti-atherogenic effects and suppresses the adipocyte differentiation in vitro. Herein, we characterized molecular mechanisms underlying the anti-adipogenic effects of oleuropein on 3T3-L1 cells and adipocytes derived from stromal-vascular fraction of dorsolumbar and gonadal fat dissected from mice. We found that oleuropein (>100 μM) decreased viability of preadipocytes proliferating in vitro and did not exerted any cytotoxic effects in post-confluent cells after induction of differentiation. Oleuropein (>100 μM) inhibited adipocyte differentiation, suppressed gene expression of peroxisome proliferator-activated receptor γ (PPARγ), CCAAT-/enhancer-binding protein α, sterol regulatory element-binding transcription factor 1c and fatty acid synthase. Furthermore, we tested ability of oleuropein to regulate of PPARγ-, PPARα- or PPARβ-/PPARδ-mediated β-lactamase expression in appropriate reporter gene assays. Oleuropein between 10 and 400 μM concentrations did not affect activity of PPARα or PPARβ/δ. Contrary, PPARγ activity, either basal or rosiglitazone activated, was inhibited by oleuropein. Our data suggest that oleuropein exerts anti-adipogenic effect through direct inhibition of PPARγ transcriptional activity.